Navigating the Road to Safer Travel in Pakistan: A Multi-Perspective Analysis of Road Safety Challenges and Solutions - Amjad Pervez; Ammar Oad (Sir Syed University Research Journal of Engineering and Technology, 2023)
With the growing global population, the demand for mobility and well-managed modes of transportation is increasing day by day. However, the rapid growth in motorization is a double-edged sword. On one side, it brings social and economic development; on the other, it results in severe consequences, such as road traffic crashes. Pakistan, a developing country, is also dealing with the same issue. Therefore, this paper aims to explore the road safety issues in Pakistan. The analysis is carried out from five perspectives: infrastructural, institutional, socio-economic, socio-cultural/behavioral, and educational. The study highlights that inadequate road infrastructure, lack of road safety institutions and policies, absence of a credible crash reporting system, poor and ineffective enforcement, road users’ aberrant behaviors, and lack of road safety awareness all contribute to road safety problems in Pakistan. To address these issues, the study proposes a set of key measures, such as expanding road infrastructure, establishing dedicated road safety institutions, centralizing data collection efforts, implementing comprehensive safety tests for vehicles, and organizing road safety seminars to educate the youth. These recommendations aim to enhance road safety, ultimately reducing fatalities and economic losses caused by road crashes in Pakistan.